Rapid species identification of "Streptococcus milleri" strains by line blot hybridization: identification of a distinct 16S rRNA population closely related to Streptococcus constellatus. - Jacobs, J A (1996)
A collection of 399 "Streptococcus milleri" strains were identified to the species level by the use of a line blot assay. Their PCR-amplified partial 16S rRNA gene sequences were hybridized with species-specific 5'-biotinylated oligonucleotide probes homologous to the bp 213 to 231 regions of the 16S rRNA gene sequences of the type strains Streptococcus anginosus ATCC 33397, Streptococcus constellatus ATCC 27823, and Streptococcus intermedius ATCC 27335. The hybridization results were compared with the reference phenotypic identification method data (R. A. Whiley, H. Fraser, J. M. Hardie, and D. Beighton, J. Clin. Microbiol. 28:1497-1501, 1990). Most strains (357 of 399 [89.5%]) reacted unambiguously with only one probe. However, 42 of the 399 strains (10.5%) reacted with both the S. constellatus- and S. intermedius-specific probes; 41 of them were phenotypically identified as S. constellatus. These dually reactive strains hybridized with a 5'-biotinylated probe based on the bp 213 to 231 region of the 16S rRNA gene sequence of one of two species. Analysis of the 5' ends of the 16S rRNA gene sequences (487 bp) demonstrated that the dually reactive strains represent a distinct rRNA population sharing 98.1% sequence similarity with S. constellatus. Phenotypic consistency between the dually reactive strains and the S. constellatus strains was not demonstrated. Line blot hybridization proved to be a simple and inexpensive method to screen large numbers of strains for genetic relatedness, and it allowed the detection of a distinct 16S rRNA type within the "S. milleri" group.